The transcription factor AtHB23 modulates starch turnover for root development and plant survival under salinity - Perotti, María Florencia; Arce, Agustin L; Ariel, Federico D; Figueroa, Carlos M; Chan, Raquel Lía (Elsevier, 2022)
AtHB23 is a homeodomain-leucine zipper I transcription factor, previously characterized as a modulator of lateral root initiation and higher-order roots development. The role of this gene in response to salinity stress was largely unknown. To elucidate the role of AtHB23 in response to salinity stress, we combined histochemical β-glucuronidase (GUS) analysis, root phenotyping, starch staining, optic and transmission electron microscopy, expression studies by RT-qPCR, and transcriptome analysis of silenced, overexpressor, and crossed plants. We revealed that the expression pattern of AtHB23 is regulated by NaCl in the primary and lateral roots, affecting the root phenotype. A severe reduction in primary root length, a significant increment in the initiation of lateral roots, and a low survival rate in salinity conditions were observed in AtHB23-silenced plants, whereas AtHB23 overexpressors showed the opposite phenotype. These developmental defects were explained by the degradation of starch granules and an alteration in starch metabolism. The AtHB23-target gene LAX3 is repressed in the tip of the primary root and affected by NaCl. We conclude that the lack of AtHB23 severely compromises plant survival and adaptation to salt stress conditions because this gene mediates starch granule turnover.
Keywords: Raíces (Botánica) - Fisiología; AtHB23; Homeodomain-leucine zipper; HD-Zip I; Root development